2001
DOI: 10.1046/j.1440-1622.2001.02189.x
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic leak in colorectal surgery: A single surgeon’s experience

Abstract: Anastomotic leakage may be minimized by ensuring that patients are as fit as possible prior to surgery, stomata are used liberally, particularly in emergency patients, and a good anastomotic technique is utilized at all times. Despite these precautions some patients will still develop a leak and if timely and appropriate action is taken the majority will survive and have their stomata closed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
45
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 27 publications
9
45
1
Order By: Relevance
“…In fact, of the 13 patients postoperative respiratory symptoms appeared to be an early indicator of an anastomotic leak. This is consistent with the findings of Isbister in his analysis of over 2,000 patients on a colorectal database (29 of whom were found to have an anastomotic leak) [18]. This author showed that patients with a leaking anastomosis were more likely to have postoperative respiratory problems than patients without leak (55.2% vs. 24.0%, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…In fact, of the 13 patients postoperative respiratory symptoms appeared to be an early indicator of an anastomotic leak. This is consistent with the findings of Isbister in his analysis of over 2,000 patients on a colorectal database (29 of whom were found to have an anastomotic leak) [18]. This author showed that patients with a leaking anastomosis were more likely to have postoperative respiratory problems than patients without leak (55.2% vs. 24.0%, respectively).…”
Section: Discussionsupporting
confidence: 86%
“…Major abdominal surgery, including the upper GI, HPB and colorectal resections, has a high incidence of minor and major complications [4,15]. Diagnosis and treatment of these complications (classified according Clavien-Dindo) are important in order to reduce further morbidity and mortality [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Others have used radiologic evidence to define anastomotic bowel leak. These also include subclinical leaks [16,17]. Therefore, it is difficult to compare studies accurately.…”
Section: Discussionmentioning
confidence: 99%